A Study onthe Social Problems of Urbanisation - s, Nivithra. (International Journal of Psychosocial Rehabilitation, 2020)
Due to India’s adoption over mixed economy after independence, it resulted to accelerate urbanisation in the country, which paved the way to the development of the private sector. Urbanisation is a ubiquitous and global phenomenon. Moreover urbanisation is now a universal, predominant, inescapable and wide- ranging phenomenon. In recent years all over the world, many nations is undergoing lots of challenging in social, economic, institutional, religious, environmental and transportation issues in their developed and developing cities. Such issues are predominantly seen in developing countries due to the development differences among the developed cities and under developed villages. The main reason behind such differences is due to more focus over the cities than in rural areas. On focusing over India, urbanisation is a pandemic and swarming problem due to uncontrolled migration. Due to the impacts of urbanisation India is facing a large number of social problems now. Convenience sampling method is adopted in this study in order to collect the samples. Where the population element are chosen for inclusion in the sample based on the ease of access. The total number of samples of responses were collected is 1638. The statistical tool used in the study are chi-square test and correlation. New implementation of programs and guidelines should be brought back soon in order to keep and maintain the social issues due to urbanisation under control.